Analisis Tingkat Kepuasan Konsumen Pada Restoran Menggunakan Logika Fuzzy Tsukamoto - Harahap, Inun Suryani; Santoso, Heri (Journal of Information System Research (JOSH), 2024)
Tsukamoto fuzzy logic method is used to measure the level of customer satisfaction at Mixue Restaurant. The background of this study is the importance of understanding and improving customer satisfaction in the highly competitive restaurant industry. Mixue attracts the attention of many people, especially students, as one of the restaurants that offers contemporary drinks at affordable prices. Mixue Jamin Ginting, Medan, questionnaires were distributed to 100 people to conduct this study. The variables analyzed were service quality, location, price, and facilities. By using the Fuzzy Tsukamoto method, consumer satisfaction values ​​in fuzzy sets such as "very satisfied", "satisfied", and "dissatisfied" were created. The results showed that the level of customer satisfaction was influenced by complete facilities, low prices, strategic location, and friendly service. This study improves Mixue management's understanding of consumer expectations and needs and the development of science in the application of fuzzy logic to consumer satisfaction analysis. The Tsukamoto fuzzy method allows for a more in-depth analysis of consumer preferences and perceptions, and helps in creating appropriate improvement strategies to improve Mixue consumer satisfaction. In a study to determine the level of consumer satisfaction at Mixue Tuntungan Deli Serdang using the fuzzy tsukamoto technique, the numerical value of the facility variable was found to be 71, the price variable was 61, the service quality facility was 58 and the location variable was 52.